Rehabilitation of a patient with cleft palate using a hollow lightweight fixed prosthesis - S Jagrathi; Chethan Hegde (Wolters Kluwer Medknow Publications, 2023)
Cleft lip and palate are the most common orofacial anomalies affecting the quality of life of an individual. Bilateral cleft lip and palate are the most difficult to treat due to missing premaxilla, and removable prosthesis is the only treatment in such situations to satisfy esthetics, function, and phonetics. In this case report, we have discussed a novel technique of rehabilitating a bilateral cleft palate patient with a fixed hollow prosthesis that would replace the missing hard and soft tissue, yet is light weighed. This unique prosthetic solution could set a new standard of treatment in a seemingly compromised situation.